Cerebral large artery occlusion in chronic graft-versus-host disease: A case report. Issue 51 (23rd December 2021) - Li, Ying; Gao, Feng; Sun, Wei; Wang, Zhaoxia; Jin, Haiqiang
Abstract: Rationale: Cerebral large artery occlusion in chronic central nervous system graft-versus-host disease after allogeneic hematopoietic stem cell transplantation (allo-HSCT) was very scarce. We described a young patient with bilateral white matter lesions and symptomatic internal carotid artery occlusion after allo-HSCT with the history of aplastic anemia. Patient concerns: A 17-year-old girl with the history of aplastic anemia developed recurrent headache and sudden hemiplegia of right limbs 2 years after allo-HSCT. Diagnoses: She was diagnosed with skin chronic graft-versus-host disease 19 months after allo-HSCT. Brain magnetic resonance imaging showed bilateral subcortical white matter abnormal signals and hyperintensity of left fronto-parietal lobe on diffusion weighted imaging and corresponding hypointense apparent diffusion coefficients indicating acute infarction. CT angiography revealed thrombosis in left internal carotid artery. Carotid plaque high-resolution magnetic resonance imaging showed annular enhancement of vascular wall revealing signs of vasculitis. Interventions: Intravenous immunoglobulin, methylprednisolone, and anticoagulant therapy were used to treat the patient. Outcomes: The patient's symptoms gradually resolved and she could walk with assistance after 3 weeks before returned home. Lessons: Chronic graft-versus-host disease-associated vasculitis could involve cerebral large vessels which warrants further study.